Subcellular localization of microcystin in the liver and the gonads of medaka fish acutely exposed to microcystin-LR. (1st March 2019) - Qiao, Qin; Djediat, Chakib; Huet, Hélène; Duval, Charlotte; Le Manach, Séverine; Bernard, Cécile; Edery, Marc; Marie, Benjamin
Abstract: Among the diverse toxic components produced by cyanobacteria, microcystins (MCs) are one of the most toxic and notorious cyanotoxin groups. Besides their potent hepatotoxicity, MCs have been revealed to induce potential reproductive toxicity in various animal studies. However, little is still known regarding the distribution of MCs in the reproductive organ, which could directly affect reproductive cells. In order to respond to this question, an acute study was conducted in adult medaka fish (model animal) gavaged with 10 μg.g −1 body weight of pure MC-LR. The histological and immunohistochemical examinations reveal an intense distribution of MC-LR within hepatocytes along with a severe liver lesion in the toxin-treated female and male fish. Besides being accumulated in the hepatocytes, MC-LR was also found in the connective tissue of the ovary and the testis, as well as in oocytes and degenerative spermatocyte-like structures but not spermatocytes. Both liver and gonad play important roles in the reproductive process of oviparous vertebrates. This observation constitutes the first observation of the presence of MC-LR in reproductive cells (female, oocytes) of a vertebrate model with in vivo study. Our results, which provide intracellular localization of MC-LR in the gonad, advance our understanding of the potential reproductive toxicity of MC-LR in fish. Highlights: MC penetrates into chorion, yolk vesicles and cytoplasm of oocytes in fish. MC was remarkably detected in degenerated germ cell-like structures in the testis. An apparent distribution of MC in oocytes of vertebrates is observed with in vivo condition for the first time.